Legal Analysis Related To The Implementation Of Government Regulation Number 22 Of 2021 Concerning The Implementation Of Environmental Protection And Management For The B3 Waste Management Company Pt Dame Alam Sejahtera - Holmen Siahaan; Yuniar Rahmatiar; Muhamad Abas; Ethan Lim kong (Faculty of Law, Universitas Pekalongan, 2025)
Article 28H paragraph 1 of the Constitution contains the right of everyone to live with happiness in birth and mind and to get a good and healthy environment which means free from pollution, safe from the dangers of hazardous waste. The presence of derivative regulations of Government Regulation No. 22 of 2021, which regulates the Implementation of Environmental Protection and Management (P3LH) creates even clearer rules, especially related to B3 Waste management The presence of the B3 Waste management industry is needed as a party that manages B3 Waste from waste producers, especially when these producers do not have the ability or facilities to manage it themselves. One of the industries managing B3 Waste, PT Dame Alam Sejahtera, has implemented Government Regulation No. 22 of 2021 concerning P3LH that has environmental approval that has been determined by the Central Government, in this writing using an empirical legal research method. The conclusion in this study is that the implementation of Government Regulation No. 22 of 2021 concerning P3LH is considered more complex than previous regulations, especially related to the change of management permits to technical approvals according to B3 Waste management activities, and administrative sanctions as per article 508 paragraph 1.Government Regulation No. 22 of 2021 concerning PP3LH, such as written reprimands to revocation of permits, is a strategic step to uphold environmental justice and responsibility in a preventive and persuasive manner, without directly applying criminal sanctions.